Design and Testing of a Computer Security Layer for the Lin Bus † - Kaschel-Carcamo, H; Paez-Mejias, F (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Most modern vehicles are connected to the internet via cellular networks for navigation, assistance, etc. via their onboard computer, which can also provide onboard Wi-Fi and Bluetooth services. The main in-vehicle communication buses (CAN, LIN, FlexRay) converge at the vehicle’s onboard computer and offer no computer security features to protect the communication between nodes, thus being highly vulnerable to local and remote cyberattacks which target the onboard computer and/or the vehicle’s electronic control units through the aforementioned buses. To date, several computer security proposals for CAN and FlexRay buses have been published; a formal computer security proposal for the LIN bus communications has not been presented. So, we researched possible security mechanisms suitable for this bus’s particularities, tested those mechanisms in microcontroller and PSoC hardware, and developed a prototype LIN network using PSoC nodes programmed with computer security features. This work presents a novel combination of encryption and a hash-based message authentication code (HMAC) scheme with replay attack rejection for the LIN communications. The obtained results are promising and show the feasibility of the implementation of an LIN network with real-time computer security protection. © 2022 by the authors.
Keywords: computer security; in-vehicle networking; LIN; encryption; HMAC; microcontroller; PSoC